The Role of Social Studies Education toward Students’ Readiness in Facing Globalization: Social Skills as Moderating Factor - Dina, Anggit Maulud; Widiastuti, Anik; Sudrajat, Sudrajat (Jurnal Pendidikan Progresif, 2024)
The Role of Social Studies Education towards Students’ Readiness in Facing Globalization: Social Skills as Moderating Factor. Objective: This study aims to determine the role of social studies education in students' readiness to face globalization through social skills. Methods: This study used a quantitative approach, utilizing data from 40 junior high school students.   Data was collected through a questionnaire using Google Forms on the role of social studies education in preparing students to face globalization through social skills. The data was analyzed using the Structural Equation Modeling -Partial Least Square (SEM-PLS) statistical testing method to construct four latent variables: social studies learning, social skills, globalization readiness, and attitudes toward adversity and globalization. Findings: SEM analysis indicates that Social Education directly influences social skills. Conversely, social skills directly impact preparation and attitudes toward difficulties and globalization. Social skills modulate the learning of Social Studies regarding attitudes towards difficulties and globalization, but do not influence the readiness for facing globalization in Social Studies learning. Conclusion: This study implies that globalization significantly influences social studies education, necessitating the cultivation of new social skills and competencies to equip students and instructors for a globally interconnected environment. This include promoting critical thinking, cultural understanding, and adaptation to manage the intricacies of global integration. Keywords: social sciences, social skills, education, globalization.DOI: http://dx.doi.org/10.23960/jpp.v14.i3.2024136